The Rigidity of Public Space for Children's Use (Play): Case of: The First November Square - Batna Province (Algeria) - Guettafi, Lamisse; Alkama, Djamel; Barrou, Djemaa (Indonesian Journal of Social Science Research, 2024)
The presence of children in public spaces has become a trigging reality to consider, because children use these spaces to play without taking into account their suitability for such activity. This article tackles children's use of the public square as a play space in Batna Province, Algeria. We adopted a mixed methodology that combines qualitative and quantitative elements to study the use and quality of a space used by children. The qualitative component allows us to explore human interactions and the environment, while the spatial analysis gives us an understanding of the physical layout of the context. The quantitative component aims to evaluate the opinions and preferences of children’s carers. To carry out this study, we conducted a field investigation, including direct observation on the site and interviews with children's carers in the square to find out their assessment and opinions on the quality of the space and its use. Moreover, an analytical study of the square plan was also implemented at the spatial and functional level, in order to reveal all the changes in space before and after use by children. The results of the study confirmed the lack of ease and flexibility of this space for use by children, and the results of the interview emphases the achieved findings, because the public space did not take the child as a user of it at all, neither in terms of space, nor planning and equipment, which led to falling into excessive use of it that resulted in lots of problems.